A survey of solar wind conditions at 5 AU: a tool for interpreting solar wind-magnetosphere interactions at Jupiter - Ebert, Robert W.; Bagenal, Fran; McComas, David J.; Fowler, Christopher M. (Frontiers in Astronomy and Space Sciences, 2014)
We examine Ulysses solar wind and interplanetary magnetic field (IMF) observations at 5 AU for two ~13 month intervals during the rising and declining phases of solar cycle 23 and the predicted response of the Jovian magnetosphere during these times. The declining phase solar wind, composed primarily of corotating interaction regions and high-speed streams, was, on average, faster, hotter, less dense, and more Alfvénic relative to the rising phase solar wind, composed mainly of slow wind and interplanetary coronal mass ejections. Interestingly, none of solar wind and IMF distributions reported here were bimodal, a feature used to explain the bimodal distribution of bow shock and magnetopause standoff distances observed at Jupiter. Instead, many of these distributions had extended, non-Gaussian tails that resulted in large standard deviations and much larger mean over median values. The distribution of predicted Jupiter bow shock and magnetopause standoff distances during these intervals were also not bimodal, the mean/median values being larger during the declining phase by ~1 – 4%. These results provide data-derived solar wind and IMF boundary conditions at 5 AU for models aimed at studying solar wind-magnetosphere interactions at Jupiter and can support the science investigations of upcoming Jupiter system missions. Here, we provide expectations for Juno, which is scheduled to arrive at Jupiter in July 2016. Accounting for the long-term decline in solar wind dynamic pressure reported by McComas et al. (2013), Jupiter’s bow shock and magnetopause is expected to be at least 8 – 12% further from Jupiter, if these trends continue.